REVIEW OF CLINICAL AND PARACLINICAL CHARACTERISTICS AND TREATMENT RESULTS OF PATIENTS WITH PRIMARY IMMUNE THROMBOCYTOPENIA AT NGHE AN GENERAL FRIENDSHIP HOSPITAL IN 2023. (Vietnam Journal of Community Medicine, 2024)
Research objective: Review the clinical and paraclinical characteristics and treatment results of patients with primary immune thrombocytopenia at Nghe An General Friendship Hospital in 2023.Research methods: A descriptive study reported a series of cases of 53 patients with primary immune thrombocytopenia treated at the Department of Clinical Hematology, Nghe An General Friendship Hospital, from January to December 2023.Research results: The average age in the study group was 50.6± 21.8 years old; The most common age group is 35-60 years old, accounting for 35.8%; Females account for a high rate of 81.1%; male/ female ratio = 1/4.3. Clinical characteristics: 96.2% (51/53) of patients were hospitalized for bleeding reasons; Spontaneous bleeding accounts for a high rate of 98.1%, of which simple subcutaneous bleeding accounts for the highest rate of 69.8%; Polymorphic haemorrhage forms account for the majority (79.2%). Paraclinical characteristics: The average platelet count at admission was 11.3 ± 8.4; 45.28% of patients had mild anaemia. The primary treatment regimen is conventional corticosteroids, accounting for 94.3%; The response rate to traditional corticosteroid regimens is 94.3%.Conclusion: Primary immune thrombocytopenic is expected in the age group of 35 - 60 years old, with spontaneous bleeding, subcutaneous bleeding and simple bleeding forms accounting for the main proportion. Patients have a high response rate to treatment, with younger age groups responding lower than middle-aged and elderly groups.
Keywords: Huu Nghi Hospital